Security issues in VANET - Sakib, Rizwanul Karim; Reza, Bisway (Department of Electronics and Communication Engineering, BRAC University, 2010)
A Vehicular Ad-Hoc Network or VANET is a form of Mobile Ad-Hoc Network or MANET which provides communication between vehicles and between vehicles and road-side base stations. A vehicle in VANET is considered to be an intelligent mobile node capable of communicating with its neighbors and other vehicles in the network. VANET is different from MANET due to high mobility of nodes and the large scale of networks. Security and privacy are the two main concerns in designing a VANET .Although there are many proposed solutions for improving securities in VANET but security still remains a delicate research subject. The main objectives of this paper is to improve the security issues in VANET.The preliminary efforts were focused on the potential applications, possible attacks, security requirements and the literature review. The long term goal of this project is to come up with an entirely new solution that can be implemented in designing a VANET.